2017
DOI: 10.1186/s13068-017-0991-x
|View full text |Cite
|
Sign up to set email alerts
|

Development and use of a switchgrass (Panicum virgatum L.) transformation pipeline by the BioEnergy Science Center to evaluate plants for reduced cell wall recalcitrance

Abstract: BackgroundThe mission of the BioEnergy Science Center (BESC) was to enable efficient lignocellulosic-based biofuel production. One BESC goal was to decrease poplar and switchgrass biomass recalcitrance to biofuel conversion while not affecting plant growth. A transformation pipeline (TP), to express transgenes or transgene fragments (constructs) in these feedstocks with the goal of understanding and decreasing recalcitrance, was considered essential for this goal. Centralized data storage for access by BESC me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…There were many interesting potential functions amongst this narrowed down set, which include several sugar transporters, two separate homologs to coumarate-coA ligases, two genes involved in glutathione S-conjugation, and several stress response genes. Other studies have found other genes such as FBA1 [ 52 ], BURP [ 53 , 54 ], USP [ 55 ], GH16_XET [ 56 ], CYP707 gene family [ 57 ], HSF [ 58 ], AAI_LTSS [ 59 ] (Additional file 1 : Table S1) to be involved in drought resistance that we would have expected to be important in this study but did not show species-specific signatures in this study. The genes we report these here so that future studies of local adaptation might use them for comparison.…”
Section: Resultsmentioning
confidence: 52%
“…There were many interesting potential functions amongst this narrowed down set, which include several sugar transporters, two separate homologs to coumarate-coA ligases, two genes involved in glutathione S-conjugation, and several stress response genes. Other studies have found other genes such as FBA1 [ 52 ], BURP [ 53 , 54 ], USP [ 55 ], GH16_XET [ 56 ], CYP707 gene family [ 57 ], HSF [ 58 ], AAI_LTSS [ 59 ] (Additional file 1 : Table S1) to be involved in drought resistance that we would have expected to be important in this study but did not show species-specific signatures in this study. The genes we report these here so that future studies of local adaptation might use them for comparison.…”
Section: Resultsmentioning
confidence: 52%
“…Cell wall lignin is one of the main causes of recalcitrance, which limits efficient conversion of biomass into biofuels (Chen and Dixon, 2007;David and Ragauskas, 2010). Cell wall components have been key targets to reduce feedstock recalcitrance; manipulating cell wall biosynthesis gene expression has been the primary strategy (Nelson et al, 2017;Biswal et al, 2018;Brandon and Scheller, 2020). Several studies with transgenic plants have been conducted in greenhouses under tightly controlled environmental conditions and the actively growing green tissue has been analyzed most often (Fu et al, 2011a(Fu et al, ,b, 2012Xu et al, 2011;Shen et al, 2012Shen et al, , 2013Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ], Prosopis spp. [ 7 ], Parthenium hysterophorus L. [ 8 ], Cannabis sativa L. [ 9 ], Panicum virgatum L. [ 10 , 11 ] and Arundo donax L. [ 12 ].…”
Section: Introductionmentioning
confidence: 99%